Mid- and long-term clinical results of the Elektra and Moovis prosthesis for trapeziometacarpal joint replacement - Frey, Pia-Elena; Bühner, Christin; Falkner, Florian; Harhaus-Wähner, Leila; Panzram, Benjamin (BMC musculoskeletal disorders, 2024)
BACKGROUND: Total joint arthroplasty as a surgical treatment option for trapeziometacarpal joint arthritis is recently revived. The aim of this study is to report on mid- and long-term results of the Elektra (single-mobility) and Moovis (dual-mobility) prosthesis for treatment of primary thumb carpometacarpal joint arthritis. - METHODS: In this retrospective, monocentric, descriptive cohort study, 31 prostheses were evaluated that were implanted by a single surgeon in 26 patients between 2009 and 2019. Indication for surgery was trapeziometacarpal joint osteoarthritis (Eaton/Littler Stage II and III). Clinical and radiological follow-up was performed at a minimum of 24 months. The postoperative assessment included range of motion, pain, strength as well as functional scores (DASH, MHQ). Implant survival and complications were the primary endpoints. - RESULTS: 10 Elektra and 21 Moovis prostheses were implanted between 2009 and 2019 with a mean follow-up of 74.2 months in the Elektra and 41.4 months in the Moovis group. The average patients' age at surgery was 64 years. Postoperative pain levels (VAS 0-10) were below 2 at rest and under stress in both groups. Grip/pinch strength and range of motion showed results comparable to the contralateral hand. Opposition was excellent with an average Kapandji index of 9.6 in both groups. Elektra achieved slightly better functional scores in the DASH and MHQ score. Satisfaction was high in both groups, and 96% of the patients would recommend the procedure. Metacarpophalangeal hyperextension > 15° was seen in 3 patients per group preoperatively and was corrected to < 5° post-surgery. 3 Elektra prostheses were revised due to cup loosening and dislocation for cup and/or neck replacement or secondary trapeziectomy. 1 Moovis prosthesis was revised with an exchange of the neck to a larger size due to restricted movement. After the mean follow-up of 7.9 years in Elektra and 3.5 years in MOOVIS, cumulative survival was 68.6% vs. 95.2%, respectively. - CONCLUSIONS: In this mid- to long-term retrospective analysis, total joint arthroplasty in primary trapeziometacarpal joint arthritis results in low pain levels, excellent mobility and clinical function. Patient satisfaction is overall high. While revision due to cup loosening occurred more often in patients with single-mobility implants, no cases of dislocation or loosening of components were observed in the dual-mobility group. - TRIAL REGISTRATION: The study was conducted in accordance with the Declaration of Helsinki, and approved by the Ethics Committee of the Medical Faculty of Heidelberg University, reference number S-150/2020.
Gesehen am 07.03.2025